A Novel Secret Location Sharing Scheme for the Wireless Sensor Network - Saikia, Monjul (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2021)
The wireless sensor network is a collection of sensor nodes that operate collectively to gather sensitive data from a target area. During the process of data collection, the location of sensor nodes from which data is originated is important when making decisions at the base station. Location, i.e., the coordinates of a sensor node, need to be shared among other nodes in various circumstances such as the key distribution phase, during the routing of packets, etc. Since the location of every sensor node must be kept secret, a scheme that facilitates secure location sharing among sensor nodes is crucial. In this paper, we propose a novel, secure, and robust mechanism for location sharing using a two-threshold scheme. The implementation process of the proposed model is shown here along with results and analysis.